Characteristics of electron injection at the oxide electrode/polyethylenimine ethoxylated/Alq3 interface. (11th December 2019) - Morimoto, Masahiro; Yoshida, Taishi; Naka, Shigeki; Okada, Hiroyuki
Abstract: Inverted organic light-emitting diodes (inverted OLEDs) require electron injection to an organic semiconductor from a transparent oxide electrode. Polyethylenimine ethoxylated (PEIE) has attracted considerable attention as an electron injection material. An injection mechanism has been suggested; however, the barrier height of electron injection has not been determined. In this paper, we present the experimental values for the electron injection barrier height at the transparent oxide electrode/PEIE/organic semiconductor interface. Electron-only devices, consisting of indium-tin-oxide (ITO)/PEIE/tris(8-hydroxyquinolinato) aluminum (Alq3 )/Al, are fabricated. The temperature dependence of the current–voltage curves is measured corresponding to the electron injection of the ITO/PEIE/Alq3 interface. The current–voltage curves are found to be independent of the measurement temperature, which is explained by the tunneling model. The tunneling injection barriers height are calculated, and the experimental injection barrier height will be important for the development of inverted OLED devices.